2018
DOI: 10.3390/antibiotics7040106
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of the Use of Point-of-Care C-Reactive Protein Testing to Reduce Antibiotic Prescribing in Primary Care

Abstract: More appropriate and measured use of antibiotics may be achieved using point-of-care (POC) C-reactive protein (CRP) testing, but there is limited evidence of cost-effectiveness in routine practice. A decision analytic model was developed to estimate the cost-effectiveness of testing, compared with standard care, in adults presenting in primary care with symptoms of acute respiratory tract infection (ARTI). Analyses considered (1) pragmatic use of testing, reflective of routine clinical practice, and (2) testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 29 publications
1
56
0
Order By: Relevance
“…After full-text evaluation, 152 publications were relevant for POCT. After excluding 34 publications [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ] ( Supplementary Materials ), 13 studies [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ] reported across 22 publications [ 61 , 62 , 63 …”
Section: Resultsmentioning
confidence: 99%
“…After full-text evaluation, 152 publications were relevant for POCT. After excluding 34 publications [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ] ( Supplementary Materials ), 13 studies [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ] reported across 22 publications [ 61 , 62 , 63 …”
Section: Resultsmentioning
confidence: 99%
“…Restricting or addressing inappropriate pharmaceutical company activities is particularly important in LMICs, where companies can be the principal source of physician education regarding antibiotics 330,331 . Selective point-of-care testing is seen as potentially beneficial in patients with URTIs 101,332 , and decision support systems have been shown to reduce the overuse of antibiotics in ambulatory care settings 333 . Social norm feedback among physicians can also appreciably reduce antibiotic prescribing in ambulatory care 334 .…”
Section: Venezuelamentioning
confidence: 99%
“…Since published data indicate that patients older than 16 years of age represent the majority of patients receiving antibiotics, the most frequently prescribed antibiotics for patients 16 years and older was used to generate an average antibiotic cost of £1.21 per ARI episode 40 . A dispensing fee of £1.90 was added to the average antibiotic cost and was assumed to be included for every prescription, based on the mean dispensing rate per item for pharmacists 41 . Out-ofpocket payments for prescription charges applicable to these medicines were not included.…”
Section: Antibiotic Cost Assumptionsmentioning
confidence: 99%